Crustal Formation on a Spreading Ridge Above a Mantle Plume: Receiver Function Imaging of the Icelandic Crust - Jenkins, J; Maclennan, J; Green, RG; Cottaar, S; Deuss, AF; White, RS (American Geophysical Union (AGU), 2018)
Abstract Iceland sits astride a mid‐ocean ridge underlain by a mantle hot spot. The interplay of these two geological processes has the potential to generate a complex and laterally variable crustal structure. The thickness of the Icelandic crust is a long running and controversial debate, with estimates ranging from a thin 20‐km crust to a thick 40‐km crust. We present new images of the first‐order seismic discontinuity structure of the Icelandic crust based on a joint inversion of receiver function and ambient noise‐derived surface wave dispersion data. Inversion results are validated through comparison to receiver functions multiphase common conversion point stacks across the densely instrumented Northern Volcanic Zone. We find a multilayered crustal structure consisting of a 6‐ to 10‐km‐thick upper crust underlain by either one or two discontinuities. The shallower discontinuity is found at depths of ≈20 km throughout Iceland. The deeper discontinuity is only present in some regions, defining the base of a lens‐like lower layer with maximum depths of 44 km above the center of the mantle plume. Either of these two discontinuities could be interpreted as the seismic Moho, providing an explanation why previous estimates of crustal thickness have diverged. Such structure may form via underplating of a preexisting oceanic crust as has been hypothesized in other ocean island plume settings. However, we demonstrate with a simple petrological model that variability in seismic discontinuity structure can also be understood as a consequence of compositional variation in melts generated with distance from the plume center.